Evaluation of the Effects of the Quaternary Ammonium Silane K21 on Zebrafish Viability, Toxicity, Growth, and Development - Surendra K. Rajpurohit; Devan Anmol S. Manhiani; Ashwin Ajith; Pragya Rajpurohit; Simran Hotwani; Sai Nasanally; Arsha Sreekumar; Keshu Bhat; Aiden Van Derhei; Rohan Pasi; Arishia Mishra; Kirk Kimmerling; et al. (Biomedicines, 2025)
Background: The FDA-cleared antimicrobial quaternary ammonium silane K21 is recognized for its antimicrobial properties. This study explored potential applications of the K21 molecule in human health protection, disease prevention, and treatment using the zebrafish model. Method: A multi-dimensional approach was utilized to assess the toxicity, tolerance, and optimal dosage of K21 through serial dilutions at various concentrations. Acute and chronic exposure studies were performed at different developmental stages (embryonic, larval, juvenile, and adult) to evaluate its efficacy and toxicity in wild-type (WT), Casper (transparent skin mutant), and transgenic zebrafish lines. Results: Significant weight gain was observed in the F1 generation following K21 treatment, a trend that continued into the F2 and F3 generations. The effects of K21 on lipopolysaccharide-induced inflammation were also examined in Casper NFkB:GFP transgenic lines. Treatment with K21 reduced inflammation, indicating anti-inflammatory properties. Improved hatching rates, accelerated larval development, an increased adult mass, and modest reductions in embryonic motility (less than 20%) suggested positive developmental influences. Single-cell RNA sequencing further validated the biological impacts of K21, revealing the potential activation of a novel pathway that accelerates zebrafish growth. Summary and Conclusions: These findings position K21 as a promising candidate for biomedical applications and aquaculture, warranting further investigation into its underlying molecular mechanisms. Our additional study on the effect of K21 on the artemia (brine shrimp) hatching process provide strong evidence of better hatching ratio of 90% for brine shrimp in the group with K21 drug treatment as compared to 70% in the group without the K21 drug at 24 h of treatment; the K21 drug helps the early hatching process, as observed the 90% hatching rate in 20 h K21 treatment group hatching while in the group without K21, only 40% of brine shrimps hatched.